Frequency of Left Ventricular Failure after Non-ST Elevation Myocardial Infarction - Omaira Tariq, Hassan Abbas Abdullah, Usman Javed Iqbal, Noor Anjum, Rajia Liaqat, Saba Hamid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of left ventricular failure after Non-ST elevation myocardial Infarction. Patients and Methods: This was a cross sectional study that was conducted in Cardiology department, Gulab Devi Hospital, Lahore.100 Patients presented in medical O.P.D of either gender with pre diagnosed NSTEMI (as per operational definition), NSTEMI confirmed clinically and by laboratory investigations were selected for study. Thorough history and written consent regarding study was signed by patients as well as the attendants. All the patients of LVF were labeled as per operational definition. Results: Out of 100 patients, 25 were in age group of 30-40 years whereas 75 were in age group of 41-54 years, mean age was calculated 44.06±5.63 years. There were 77% male whereas 23% of the subjects were females. Frequency of left ventricular failure was 37% after Non-ST elevation myocardial infarction. Conclusion: In this new study, we found that 37% of patients went into left ventricular failure after Non ST elevation Myocardial Infarction. The major associations of left ventricular failure were age, gender, BMI, hypertension, diabetes mellitus, smoking and dyslipidemia. Keywords: Non-ST Elevation Myocardial Infarction, Heart Failure